1990
DOI: 10.1021/bi00462a009
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl peptides of rabbit muscle pyruvate kinase labeled by the affinity label 8-[(4-bromo-2,3-dioxobutyl)thio]adenosine 5'-triphosphate

Abstract: The affinity label 8-[(4-bromo-2,3-dioxobutyl)thio]adenosine 5'-triphosphate (8-BDB-TA-5'-TP) reacts covalently with rabbit muscle pyruvate kinase, incorporating 2 mol of reagent/mol of enzyme subunit upon complete inactivation. Protection against inactivation is provided by phosphoenolpyruvate, K+, and Mn2+ and only 1 mol of reagent/mol of subunit is incorporated [DeCamp, D.L., Lim, S., & Colman, R.F. (1988) Biochemistry 27, 7651-7658]. We have now identified the resultant modified residues. After reaction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…The results of this study using dibromobutanedione are in accord with and strengthen our previous conclusions based on the reactions of bromodioxobutyl-nucleotides with pyruvate kinase (Vollmer & Colman, 1990). Cys' @' is a nonessential amino acid in the vicinity of the active site, whereas modification of CysI5' causes loss of activity, suggesting that it is at or near the active site of muscle pyruvate kinase.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of this study using dibromobutanedione are in accord with and strengthen our previous conclusions based on the reactions of bromodioxobutyl-nucleotides with pyruvate kinase (Vollmer & Colman, 1990). Cys' @' is a nonessential amino acid in the vicinity of the active site, whereas modification of CysI5' causes loss of activity, suggesting that it is at or near the active site of muscle pyruvate kinase.…”
Section: Discussionsupporting
confidence: 91%
“…In the case of DBBD, PEP protects best against the inactivation of pyruvate kinase, indicating that reaction occurs in the region of the active site, as it does with the nucleotidyl affinity reagents bearing the bromodioxobutyl arm. The specificity for the active site of the enzyme is likely due to the similarity in structure between the substrate PEP and the dioxobutyl group, which exists predominantly in the enol form (Decamp & Colman, 1989;Vollmer & Colman, 1990). Given that the bromodioxobutyl nucleotides react at the same functional site (that protected by PEP), it is not surprising that the particular residue that reacts with dibromobutanedione causing loss of activity, CYS"~, is the same residue as that which causes loss of activity upon reaction of pyruvate kinase with 8-BDB-TATP (Vollmer & Colman, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7). Although it has been indicated that inactivation of rabbit muscle PK was occurred primarily due to modification of cysteine residues in the active site, 30,31) there are little evidences of human PK. Thus, further work is required to elucidate the specific mechanism of inactivation induced by BHP-derived radicals in terms of the modification of active sites or the kinetics changes in order to detail our findings with the data observed in human RBCs under similar conditions.…”
Section: Discussionmentioning
confidence: 99%